Current antibiotic sensitivity of Lactococcus garvieae in rainbow trout (Oncorhynchus mykiss) farms from Southwestern Turkey - Mesut Yılmaz; Tülin Arslan; Sabahat Selmin Sezgin; Ayşegül Kubilay (Journal of Agricultural Sciences)
The continuity of antimicrobial resistance development in bacteria changes the type and dose of effective antibiotic treatments and makes routine monitoring studies necessary for successful control of bacterial diseases. This study was aimed to determine the current antibiotic susceptibility of Lactococcus garvieae, which causes significant economic losses in rainbow trout (Oncorhynchus mykiss) farms. In the study, two consecutive visits were made to three farms operating on the banks of a stream during a disease outbreak in the fall of 2018. At each visit, 10 fish showing the signs of disease from each farm (60 fish in total) were sampled and L. garvieae was isolated from 16 fish. All isolates were identified using conventional and molecular methods. Then, they were examined for 5 different antibiotic resistance genes and their antibiotic susceptibility profiles were determined using the Kirby Bauer disc diffusion technique. Results of the disc diffusion test revealed that all 16 isolates had a different antibiotic susceptibility profile and the isolates with different antibiotic susceptibility profile could exist within and between farms, using the same water source. Furthermore, they revealed that highly resistant isolates that showed no susceptibility up to 82 to 100% of the 33 antibiotics at the doses evaluated exist in all farms. All isolates carried either tetA or tetB genes or both and the majority of isolates carried tetA gene. Together with this, 25% of the isolates which carried both or one of the resistance genes showed susceptibility to all 4 tetracycline class antibiotics at the doses evaluated. Results of the study and their comparison with previous studies in the same production area or in different regions of the country revealed the dynamic nature of antibiotic resistance development in L. garvieae. Additionally, it showed that monitoring studies with a limited number of isolates may not give an accurate picture of the current status of antibiotic resistance from a production area. These results of the study were also discussed in terms of the treatment strategies that trout farmers should follow when treating lactococcosis.